Peran Orang Tua dalam Mendampingi Pembelajaran Di Masa Pandemi Covid 19 pada PAUD Tarbiyatul Aulad - Linda Lisyani (CV. Syntax Corporation Indonesia, 2021)
The covid-19 pandemic led to the issuance of learning from home rules for school children and work from home for teachers, including those who work in PAUD institutions. This study aims to find out how parental assistance to children at home during the current covid 19 pandemic which since March 2020 learning is done online. This article uses case study methods through interviews and observations with analysis on 25 parents and students. The results show that in general the roles that arise are as mentors, educators, guardians, developers and supervisors. In particular, the role of parents is to care for, raise, accompany, and provide a good education for children, none other than being their school learning teacher at home, supervising every task and material that the teacher gives to the child. In this case, parents play an important role in their school assistance at home during Covid 19, as well as good communication with children. Parents and teachers, so that learning can run well and effectively. Especially in the assistance of early childhood learning which is carried out at PAUD Tarbiyatul Aulad.